An intelligent location recommender system utilising multi-agent induced cognitive behavioural model. Issue 10 (26th November 2021) - Ravi, Logesh; Devarajan, Malathi; V, Vijayakumar; Sangaiah, Arun Kumar; Wang, Lipo; A, Sasikumar; Subramaniyaswamy, V
ABSTRACT: In recent times, location recommendation has received significant attention from the researchers due to emerging utilisation of Location Based Social Networks in the prediction process. In this paper, we present a new multi-agent based framework to generate better-personalised location recommendations. We address the personalisation problem through the dynamic user profile that incorporates the user's long-term and short-term cognitive behaviour. The better adaptation of user cognitive behaviour enhances the prediction process and improves overall user experience with better recommendations. A detailed user study is conducted to reveal the improved performance of proposed approach through enhanced recommendations in comparison with other approaches.